Cosas que me gustan - Browne, Anthony, 1946-; Esteva, Carmen (Mexico : Fondo de Cultura Economica, 1992)
A young chimp enumerates favorite playtime activities, from painting and riding a bike to paddling in the sea and partying with friends.
Translation of: Things I like.
In Spanish.
Keywords: Chimpanzees -- Fiction; Play -- Fiction